Relevansi Metode Pendidikan Islam Dalam Kitab Hadis Al-Arba’in An-Nawawī Dengan Metode Pendidikan Masa Kini - Junaidi Arsyad; Nawir Yuslem; Athiyah Sakinah (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
The term character is generally equated meaning with manners, manners, manners in English, and it is no different from the meaning of the word moral. The purpose of this research is to get a description of the development of noble character through a program of child-friendly schools. This study used a descriptive qualitative method. Based on the results of the research, it is known that a lack of understanding of teachers and the school community about the relevance of the policy development of noble character through the implementation of the program of child-friendly schools. It becomes an opportunity for problem-solving learning by formulating an alternative to overcome the problems encountered, through the strategy conceptual form of practical tips program, child-friendly schools, then through group discussions guided (Focus Group Discussion). Which was attended by the Head of school and teachers, supervisors SRA DKI Jakarta Province Head of JUNIOR high school Learning and academics. Strategy conceptual form of practical Tips is a step to carry out the program of child-friendly schools so that it can provide space for the teacher to pour creativity in the effort to improve the implementation of the learning and development of noble character in the child.